New records of the genus Diodontus Curtis, 1834 (Hymenoptera: Crabronidae) from Bulgaria, Montenegro and Poland, with a key to Central and Eastern European species - Olszewski, Piotr; Ljubomirov, Toshko; Wiśniowski, Bogdan; Kowalczyk, Jan Krzysztof; Krzyżyński, Maciej (Zootaxa, 2016)
First records of Diodontus medius Dahlbom, 1844 and D. insidiosus Spooner, 1938 from Poland, and of D. handlirschi Kohl, 1888 from Bulgaria and Montenegro are provided. An illustrated key for the identification of Central and Eastern European species of the genus Diodontus is given.